Work-family facilitation, job satisfaction and psychological strain among Malaysian female employees - Hussin, Ruhaya (Faculty of Management, Universiti Teknologi Malaysia, 2015)
Previously, work-family conflict has been the main focus of work and family studies in Malaysia. However, recent research has found that combining work and family domains does not always result in negative outcomes for employees. In this study, the relationships between the positive aspect of work-family interface (work-family facilitation) and job satisfaction with psychological strain among employees were tested. Additionally, the roles of job satisfaction as a mediator between work-family facilitation and psychological strain were examined. A total number of 740 female employees from several organisations in Malaysia completed the survey. The hierarchical regression and structural equation modelling analyses were conducted to analyse the data. As expected, the findings provided evidences for (i) direct effects of work-family facilitation and job satisfaction on psychological strain and (ii) mediating effects of job satisfaction on the relationship between work-family facilitation and psychological strain. The implications, limitations, and recommendations were also discussed.